The Therapeutic Potential of Umbilical Cord Mesenchymal Stem Cells in Mice Premature Ovarian Failure. (13th August 2013) - Wang, Shufang; Yu, Ling; Sun, Min; Mu, Sha; Wang, Changyong; Wang, Deqing; Yao, Yuanqing
Abstract : Mesenchymal stem cells, which are poorly immunogenic and have potent immunosuppressive activities, have emerged as promising cellular therapeutics for the treatment of several diseases. Mesenchymal-like cells derived from Wharton's Jelly, called umbilical cord matrix stem cells (UCMSCs), reportedly secrete a variety of cytokines and growth factors, acting as trophic suppliers. Here, we used UCMSCs to treat premature ovarian failure (POF). Ovarian function was evaluated by ovulation and the number of follicles. Apoptosis of the granulosa cells (GC) was analyzed by TUNEL staining. We found that after transplantation of the UCMSCs, apoptosis of cumulus cells in the ovarian damage model was reduced and the function of the ovary had been recovered. The sex hormone level was significantly elevated in mice treated with UCMSCs. The number of follicles in the treated group was higher than in the control group. Our results demonstrate that UCMSCs can effectively restore ovary functionality and reduce apoptosis of granulosa cells. We compared the RNA expression of the UCMSCs treated group with the POF model and wild-type control group and found that the UCMSC group is most similar to the wild-type group. Our experiments provide new information regarding the treatment of ovarian function failure.